The vocalization of Gastrotheca fissipes (Boulenger, 1888) (Anura, Hemiphractidae) from the state of Pernambuco, northeastern Brazil - Roberto, Igor Joventino; Santos, Ednilza Maranhão Dos; de Carvalho, Thiago Ribeiro (Zootaxa, 2019)
Gastrotheca Fitzinger, 1843 (Hemiphractidae) is composed of 70 species classified into four species groups, among which Gastrotheca fissipes (Boulenger, 1882) and G. microdiscus (Andersson, 1910) species groups are distributed in the Brazilian Atlantic Forest (Castroviejo-Fisher et al. 2015; Duellman & Venegas 2016). The Gastrotheca fissipes group comprises six species: G. fissipes, G. flamma Juncá & Nunes, 2008, G. megacephala Izecksohn, Carvalho-e-Silva & Peixoto, 2009, G. prasina Teixeira Jr. et al. 2012, G. pulchra Caramaschi & Rodrigues, 2007, and G. recava Teixeira Jr. et al. 2012, and most of these species are distributed in the northern Atlantic Forest, the most threatened region of the Atlantic Forest Domain (Ribeiro et al. 2009).